PESAN EDUKASI VIDEO YOUTUBE ASUMSI.CO "PENCURI DATA PRIBADI" DAN SIKAP MELINDUNGI DATA PRIBADI MAHASISWA PRODI ILMU KOMUNIKASI UPN "VETERAN" JAKARTA - Kayla Salwa Firdhatasha (2024)
The rise of cases of the theft and misuse of personal data in digital era has increasingly become a public concern. Accordingly, there needs to be an effort to increase public awareness and knowledge of the importance of protecting personal data. In this case, the Ministry of Communication and Informatics took steps to educate the public on how to respond to the threat of this kind of cybercrime. One of the forms of the education is a video uploaded to YouTube entitled "Pencuri Data Pribadi" which uploaded on the Asumsi.co YouTube channel. This study aims to describe and prove the effect of educational messages on the Asumsi.co YouTube video "Pencuri Data Pribadi" on how to behave towards protecting personal data by testing entertainment education theory. An explanatory quantitative approach with a survey method was carried out on active students of the Communication Science Study Program of UPN "Veteran" Jakarta. The sample was drawn using Propotionate Stratified Random Sampling. Data collection was carried out through questionnaires distributed via social media called "Line" to 93 respondents. The results showed that educational messages influence attitudes towards protecting personal data. The suggestion in this research is that the design of the video illustration concept can be reviewed so that it is more interesting and able to give a deep impression to the audience so that the educational message conveyed can stick in the hearts and minds of the audience for a long period of time. It is also recommended to test different variables such as the credibility of the communicator and the media for delivering educational messages that can influence attitudes.